Shifting Control Algorithm for a Single-Axle Parallel Plug-In Hybrid Electric Bus Equipped with EMT - Yunyun Yang; Sen Wu; Xiang Fu (Discrete Dynamics in Nature and Society)
Combining the characteristics of motor with fast response speed, an electric-drive automated mechanical transmission (EMT) is proposed as a novel type of transmission in this paper. Replacing the friction synchronization shifting of automated manual transmission (AMT) in HEVs, the EMT can achieve active synchronization of speed shifting. The dynamic model of a single-axle parallel PHEV equipped with the EMT is built up, and the dynamic properties of the gearshift process are also described. In addition, the control algorithm is developed to improve the shifting quality of the PHEV equipped with the EMT in all its evaluation indexes. The key techniques of changing the driving force gradient in preshifting and shifting compensation phases as well as of predicting the meshing speed in the gear meshing phase are also proposed. Results of simulation, bench test, and real road test demonstrate that the proposed control algorithm can reduce the gearshift jerk and the power interruption time noticeably.